2012
DOI: 10.1007/s11249-012-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Contact of a Finger on Rigid Surfaces and Textiles: Friction Coefficient and Induced Vibrations

Abstract: The tactile information about object surfaces is obtained through perceived contact stresses and friction-induced vibrations generated by the relative motion between the fingertip and the touched object. The friction forces affect the skin stress-state distribution during surface scanning, while the sliding contact generates vibrations that propagate in the finger skin activating the receptors (mechanoreceptors) and allowing the brain to identify objects and perceive information about their properties. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 42 publications
8
46
0
Order By: Relevance
“…Studies with biomimetic devices have led to the proposition that the spatial period of fingerprints would be reflected in the frequency spectrum of vibrations elicited by nonperiodic textures ). However, other studies have suggested that fingerprints merely enhance the magnitude of the elicited vibrations indiscriminately (Oddo et al 2011) or that their frequency composition depends on the ratio between the spatial period of the texture and that of the fingerprints (Fagiani et al 2011(Fagiani et al , 2012.…”
Section: Role Of Fingerprints In Texture Perceptionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies with biomimetic devices have led to the proposition that the spatial period of fingerprints would be reflected in the frequency spectrum of vibrations elicited by nonperiodic textures ). However, other studies have suggested that fingerprints merely enhance the magnitude of the elicited vibrations indiscriminately (Oddo et al 2011) or that their frequency composition depends on the ratio between the spatial period of the texture and that of the fingerprints (Fagiani et al 2011(Fagiani et al , 2012.…”
Section: Role Of Fingerprints In Texture Perceptionmentioning
confidence: 98%
“…Previous studies examining texture-elicited vibrations have focused on small sets of (mainly artificial) textures and have used techniques requiring direct skin contact Hollins 2003, 2005;Fagiani et al 2012), which might alter or impede the signal. Furthermore, the factors that shape the vibrations remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the exploratory procedure to detect the surface features of various objects consists of a sliding movement of our finger(s) at a moderate load and relatively low sliding velocity (Klatzky and Pawluk, 2013;Barnes et al, 2004). Surface recognition is deciphered by the cutaneous sensory neurons from the specific movement made by our finger during active touch (Fagiani et al, 2012). The touch perception is greatly influenced by the friction generated between the fingertip and counter-surfaces (Darden and Schwartz, 2013;Klatzky and Pawluk, 2013;Skedung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the exploratory procedure to detect the surface features of various objects consists of a sliding movement of our finger(s) at a moderate load and relatively low sliding velocity . Surface recognition is deciphered by the cutaneous sensory neurons from the specific movement made by our finger during active touch (Fagiani et al, 2012). The touch perception is greatly influenced by the friction generated between the fingertip and countersurfaces (Darden and Schwartz, 2013;Liu et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%